Analisis Komparatif Penerapan Bioteknologi pada Padi dan Jagung di Indonesia Periode 2020–2025 - Rahmah, Tsamarah Nur; Wahyuni, Dwi; Rahmah, Hanifa (Agrifo : Jurnal Agribisnis Universitas Malikussaleh, 2025)
Biotechnology plays a crucial role in addressing food security by enhancing production yields, optimizing the use of marginal land, and improving resistance to pests and diseases. However, the development of agricultural biotechnology research in Indonesia still lags significantly behind other countries. This study presents comparative information on biotechnology approaches applied to rice and corn variety development in Indonesia. The Narrative Literature Review (NLR) method was used, compiling secondary literature (journal articles/books) indexed in Google Scholar from 2020 to 2025 and integrating information on related topics through descriptive analysis. The study revealed that the application of biotechnology to rice variety development is more varied than to corn varieties. However, the application of biotechnology shares the same priority goal: producing superior rice and corn varieties in various aspects of the environment, quality, and durability. Complex policies, limited resources, and social accessibility are the main challenges facing biotechnology development in Indonesia.